Chapter Il cosmo di un signore padano del Quattrocento - Gentile, Marco (Reti Medievali E-Book, 2021)
The description of the "good death" and of the funeral of Giberto Sanvitale, count of Belforte, offers a vantage point to understand the nature and the extension of the political horizon of a member of the fifteenth century Lombard high landed nobility. This accurate and unique report highlights the relevance of personal, non-territorial ties and the importance of the organic relationship between city and countryside, strengthened by factional allegiance, in the material constitution of the lordship.